Flows in transportation networks - Potts, Renfrey B.; Oliver, Robert M. (New York : Academic Press, 1972)
This text is designed to provide a comprehensive formulation of the more important transportation models
Includes bibliographical references.
ijb 17/01/2019
Loans
Keywords: Transportation--Mathematical models